PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN KEMAMPUAN SISWA MENGGAMBAR ILUSTRASI DI KELAS IV SD NEGERI 99 PEKANBARU - Ramadani, Eka; Antosa, Zariul; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract The problem of this research of  study is the low ability students in learning to draw illustration. Based on data analysis of preliminary data on the number of students in a category it less able there are 20 students, quite capable are 5 students, then students are in the able category are 4 students with an average value of grade 48. With the background of the existing problems the researchers conducted the study with the model of Cooperative Learning Type Think Pair Share in improving  learning outcomes. The purpose from this study is to improve the ability of students to draw illustrations in the fourth grade at SDN 99 Pekanbaru with number of students are 25 students consisting of 14 male students and 11 female students. In improving learning outcomes researchers conduct classroom action research based on the design and implementation of learning syllabus performed by 3 cycles, each cycle of meetings conducted twice after learning model Think Pair Share Cooperative mode applied, so the results obtained in the first cycle students in the able category quite capable are 9 students, and less capable are 16 students with an average value of class is 58,12 class. While the end of the second cycle students are very capable are 2 students, in able category are 12 students and quite cpable there are 11 students with an average value of  class is 75,60 class. In the third cycle students are very capable increase of to 7 students and able there are 14 students with an average value of class is 83,12. Based on the results of this study it can be concluded that the application of learning models Think Pair Share Coopertive mode can improve the ability to draw illustrations fourth grade students of SDN 99 Pekanbaru.Keywords : Guided Inquiry, objects construction